The development of camera technology and effects - Boonkong, Vinai (Interdisciplinary Research Review, 2016)
At present, the advancement of technology affects the development of the camera technology, as the development of camera technology from analog system to digital system comprising still camera, video camera, and moving picture camera. The development of the camera technology has affected in the several dimensions such as mass media, educational institution and general public. Therefore, the objective of this article is to present the opinion on the positive and negative effects of the camera technological development as the result of the technological convergence.